Infection-related and Lifestyle-related Cancer Burden in Kampala, Uganda: Projection of the Future Cancer Incidence up to 2030 - Asasira, Judith; Lee, Sanghee; Mpamani, Collins; Wabinga, Henry; Park, Yikyung; Cho, Hyunsoon (BMJ open, 2022)
In Uganda, infection-related cancers have made the greatest contribution to cancer burden in the past; however, burden from lifestyle-related cancers has increased recently. Using the Kampala Cancer Registry data, we projected incidence of top five cancers, namely, Kaposi sarcoma (KS), cervical, breast and prostate cancer, and non-Hodgkin’s lymphoma (NHL) in Uganda.
Keywords: cancer; projection; Infection-related and lifestyle-related